A lithium ion battery separator and modification method
By using POSS-(PMMA)8 coating on the lithium-ion battery separator, the poor wetting and interface compatibility of the diaphragm electrolyte are solved, the mechanical properties and thermal stability are improved, the internal resistance of the battery cell is reduced, and the internal resistance of the battery is overcome. High cost and supply uncertainty of PVDF coating materials.
Patent Information
- Application Number
- CN202411164916.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-08-23
AI Technical Summary
The existing lithium-ion battery separators have problems such as poor electrolyte wetting and poor compatibility with electrode interfaces. Polyvinylidene fluoride (PVDF) is a coating material with high prices and limited output, resulting in increased cost and supply uncertainty.
Using anisole as solvent, octachloropropylsilsesquioxane as initiator, methyl methacrylate as monomer, cuprous chloride as catalyst, and pentamethyldiethylenetriamine as ligand, transfer by atomic Polymethacrylic-cage polysilsesquioxane was synthesized by free radical polymerization, and a modified slurry was prepared and coated on the surface of the membrane to form a POSS-(PMMA)8 coating.
It improves the mechanical properties and thermal stability of the diaphragm, improves the wetting properties of the electrolyte, reduces the internal resistance of the battery cell, and is cost-effective and has a stable supply.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion battery diaphragm modification, and in particular relates to a lithium ion battery diaphragm and a modification method. Background Art
[0002] The diaphragm is a functional membrane material with a microporous structure and is one of the components of lithium-ion batteries. Currently, the main commercial diaphragm materials are polyolefin diaphragms, including polyethylene (PE), polypropylene (PP) and multilayer composite diaphragms. However, polyolefins have problems such as poor wettability with electrolytes and poor interface compatibility with electrodes. To improve and solve these problems, the commonly used method is to coat the surface of polyolefin diaphragms. Inorganic nanoparticles such as silica (SiO2), alumina (Al2O3), and boehmite (AlOOH) coatings are usually used to improve mechanical properties and thermal stability, while polyvinylidene fluoride (PVDF) coatings are usually used to improve the adhesion between the diaphragm and the electrode sheet and improve the wettability of the electrolyte to the diaphragm. However, the price of PVDF is relatively high and there is a production bottleneck, which increases the uncertainty of supply and the cost of batteries.
[0003] Polymethyl methacrylate (PMMA), also known as acrylic, is low-priced and easy to process. It is also chemically stable and easily wetted by electrolytes. It has great potential in replacing PVDF diaphragm coatings. However, compared to PVDF, PMMA has a large output and a lower price, but has lower mechanical strength and is prone to scratches. Lithium dendrites generated during long-term use of lithium batteries can easily pierce the coated diaphragm, causing an internal short circuit in the battery. In addition, PMMA easily swells in the electrolyte, blocking the pores of the diaphragm, thereby hindering the transfer of lithium ions and increasing the internal resistance of the battery. Summary of the invention
[0004] 1. Technical issues to be resolved
[0005] The present invention mainly aims at the above problems and proposes a lithium-ion battery separator and a modification method, the purpose of which is to solve the problems that the polyolefin separator used in existing lithium-ion batteries has poor electrolyte wettability and poor interface compatibility with electrodes, and that polyvinylidene fluoride (PVDF) as a coating material can improve the above problems but has high prices and limited production, leading to increased costs and supply uncertainties.
[0006] (II) Technical solution
[0007] To achieve the above object, the first aspect of the present invention provides a method for modifying a lithium ion battery separator, the modification method comprising:
[0008] Polymethacrylic acid-cage polysilsesquioxane was synthesized by atom transfer radical polymerization using anisole as solvent, octachloropropylsilsesquioxane as initiator, methyl methacrylate as monomer, cuprous chloride as catalyst and pentamethyldiethylenetriamine as ligand.
[0009] The synthesized polymethacrylic acid-cage-type polysilsesquioxane is prepared into a modified slurry containing the polymethacrylic acid-cage-type polysilsesquioxane;
[0010] The modified slurry is coated on the surface of the diaphragm base film and dried to obtain a polymethacrylic acid-cage-shaped polysilsesquioxane coated diaphragm.
[0011] Furthermore, the preparation method of polymethacrylic acid-cage polysilsesquioxane includes: gradually adding anisole, octachloropropylsilsesquioxane, pentamethyldiethylenetriamine, cuprous chloride, and MMA into a flask, then placing the flask with a stopper into liquid nitrogen, using a vacuum pump to evacuate the air in the flask and fill it with high-purity nitrogen to remove oxygen and water vapor in the flask, thawing and then freezing, repeating three times, reacting at 80°C for 6-12 hours, and extracting the product by precipitation and filtration.
[0012] Furthermore, the preparation of the modified slurry includes: adding deionized water, a dispersant, polymethacrylic acid-cage polysilsesquioxane powder, a binder, a thickener and a wetting agent according to a mass ratio, and mixing and stirring.
[0013] Further, 100 parts of anisole, 1-8 parts of octachloropropylsilsesquioxane, 1-3 parts of pentamethyldiethylenetriamine, 0.5-2 parts of cuprous chloride, and 89-96 parts of MMA are gradually added into a flask, and then the flask with a stopper is placed in liquid nitrogen, the air in the flask is evacuated by a vacuum pump and high-purity nitrogen is filled in to remove oxygen and water vapor in the flask, the flask is thawed and then frozen again, and the reaction is repeated three times, and the reaction is carried out at 80° C. for 6-12 hours, and the product is extracted by precipitation and filtration.
[0014] Further, 0.3-1 parts of dispersant are added to 30-90 parts of deionized water by mass ratio, and the mixture is stirred and dispersed at a speed of 800-1200 rpm for 5-20 minutes;
[0015] Add 10-40 parts of polymethacrylic acid-cage polysilsesquioxane powder, and stir and disperse at 800-1500 rpm for 40-80 minutes;
[0016] Add 0.2-2 parts of binder, stir and disperse at 700-1000 rpm for 15-35 minutes;
[0017] Add 0.05-0.5 parts of thickener, and stir and disperse at 800-1200 rpm for 10-30 minutes;
[0018] Add 0.0001-0.01 parts of wetting agent and stir and disperse at 700-900 rpm for 25-50 minutes;
[0019] A modified slurry containing polymethacrylic acid-cage polysilsesquioxane is obtained.
[0020] Furthermore, the method further includes transferring the obtained modified slurry into a finished product container and maintaining low-speed stirring.
[0021] Furthermore, the modified slurry is coated on the surface of the diaphragm base film by gravure coating or spraying, and the moisture is dried in an oven to obtain a polymethacrylic acid-cage-shaped polysilsesquioxane coated diaphragm.
[0022] Furthermore, in the preparation process of the polymethacrylate-cage polysilsesquioxane powder, the molecular weight of the obtained polymethacrylate-cage polysilsesquioxane is adjusted by adjusting the ratio of octachloropropyl silsesquioxane to methyl methacrylate.
[0023] To achieve the above-mentioned purpose, the first aspect of the present invention provides a lithium-ion battery separator made by the modification method, comprising a polymethacrylic acid-cage polysilsesquioxane coating and a separator base film layer, wherein the polymethacrylic acid-cage polysilsesquioxane coating is formed by coating a modified slurry containing polymethacrylic acid-cage polysilsesquioxane on the surface of the separator base film.
[0024] Furthermore, the diaphragm base film is selected from one of polyethylene, polypropylene or a multi-layer composite diaphragm.
[0025] (III) Beneficial effects
[0026] Compared with the prior art, the present invention provides a lithium ion battery separator and a modification method. The present invention solves several problems of the separator in the prior art by using polymethyl methacrylate (PMMA) modified by cage-type polysilsesquioxane (POSS), namely POSS-(PMMA)8, as a coating material for the lithium ion battery separator, as follows:
[0027] 1. Improvement of mechanical properties: The inorganic skeleton of POSS molecules provides good mechanical properties and thermal stability. When these molecules are introduced into PMMA, they act as a reinforcing agent and improve the overall mechanical strength of the coating. This is because the inorganic core of POSS can act as a stress dispersion point, which can more effectively disperse and withstand stress when subjected to mechanical force, thereby reducing the possibility of damage and scratching of the material, which is particularly important for preventing lithium dendrites from penetrating the separator.
[0028] 2. Enhanced thermal stability: The inorganic components of POSS also provide high thermal stability. Under high temperature conditions, this feature can prevent thermal degradation of the separator material, thereby reducing the safety risk of lithium-ion batteries overheating. In addition, high thermal stability is also conducive to maintaining battery performance over a wide temperature range.
[0029] 3. Improved electrolyte wettability: PMMA itself has good electrolyte wettability, which means that the electrolyte can more easily penetrate the separator to ensure the effective transmission of lithium ions. The use of POSS-(PMMA)8 further optimizes this property by increasing the hydrophilic or lipophilic side chains of the material, thereby improving the electrolyte wettability and ensuring good lithium ion transmission efficiency.
[0030] 4. Reduce the internal resistance of the battery cell: Improved electrolyte wettability and optimized pore structure help reduce the transmission resistance of lithium ions in the electrolyte, thereby reducing the internal resistance of the entire battery cell. Lower internal resistance means less energy loss during charging and discharging, improving the energy utilization efficiency and charging and discharging performance of the battery.
[0031] 5. Cost and supply advantages: Compared with the use of traditional coating materials such as PVDF, the use of POSS-(PMMA)8 provides the advantages of high cost-effectiveness and stable supply, because PMMA is a commonly used and low-cost material, and its modified products can reduce production costs and market supply risks without sacrificing performance.
[0032] In summary, through the modification method of the present invention, the modified PMMA coated diaphragm technology of the present invention not only achieves remarkable results in improving the mechanical properties and thermal stability of the diaphragm, but also optimizes cost-effectiveness and supply stability while maintaining good electrolyte wettability and reducing the internal resistance of the battery cell, showing a wide range of application potential. DETAILED DESCRIPTION
[0033] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0034] The chemical formula of cage-type polysilsesquioxane (POSS) is (RSiO3 / 2) n It is an organic-inorganic hybrid material with Si-O-Si as the structural skeleton and external functionalized organic side chains. It consists of two parts, organic and inorganic.
[0035] Inorganic part: Mainly composed of Si-O-Si main chain, which provides good mechanical properties and thermal stability. This part constitutes the framework or skeleton of POSS molecule and is the source of its stability and mechanical strength.
[0036] Organic part: It is the functionalized organic side chain attached to the inorganic skeleton. These organic side chains give POSS more functionality and design potential, including its amphiphilicity. According to the number of R side chains on POSS, it can be divided into different types such as T6, T8, T12, etc. Among them, the hexahedral cage-type polysilsesquioxane structure of T8 has good symmetry and is easier to synthesize.
[0037] Specifically, in polymethacrylate-cage polysilsesquioxane (POSS-(PMMA)8), the PMMA part, i.e., polymethyl methacrylate, is the side chain, which is the organic part of the material. The side chain is connected to the inorganic main chain through a chemical bond, providing possible functions such as improving interface compatibility and adjusting hydrophobic or hydrophilic properties.
[0038] A lithium ion battery separator of the present invention comprises a polymethacrylic acid-cage polysilsesquioxane coating and a separator base film layer. The polymethacrylic acid-cage polysilsesquioxane coating is formed by coating a modified slurry containing polymethacrylic acid-cage polysilsesquioxane on the surface of the separator base film.
[0039] As a preferred method of this embodiment, the diaphragm base film is selected from one of polyethylene, polypropylene or a multi-layer composite diaphragm.
[0040] Therefore, the modification method of lithium-ion battery separator includes three parts. The first step is to prepare polymethacrylic acid-cage polysilsesquioxane (POSS-(PMMA)8), the second step is to prepare the modified slurry; and the third step is to coat the modified slurry. The preparation methods of each part are as follows:
[0041] The first step, preparation of polymethacrylate-cage polysilsesquioxane (POSS-(PMMA)8):
[0042] POSS-(PMMA)8 was synthesized by ATRP (atom transfer radical polymerization) using C7H8O (anisole) as solvent, POSS-(C3H6Cl)8 (octachloropropylsilsesquioxane) as initiator, MMA (methyl methacrylate) as monomer, CuCl (cuprous chloride) as catalyst and PMDETA (pentamethyldiethylenetriamine) as ligand. In the specific implementation process, 100 parts of C7H8O, 1-8 parts of POSS-(C3H6Cl)8, 1-3 parts of PMDETA, 0.5-2 parts of CuCl, and 89-96 parts of MMA are gradually added into a flask, and then the flask with a stopper is placed in liquid nitrogen, and the air in the flask is evacuated by a vacuum pump and filled with high-purity nitrogen to remove oxygen and water vapor in the flask, and the flask is thawed and then frozen again, and the reaction is repeated three times at 80°C for 6-12h, and the product is extracted by precipitation and filtration, and the molecular weight of the obtained POSS-(PMMA)8 is adjusted by adjusting the ratio of POSS-(C3H6Cl)8 and MMA.
[0043] Step 2: Preparation of modified slurry:
[0044] Add (0.3-1 part) of dispersant to 30-90 parts of deionized water according to the mass ratio, stir and disperse at a speed of 800-1200rpm for 5-20min; add 10-40 parts of POSS-(PMMA)8 powder, stir and disperse at a speed of 800-1500rpm for 40-80min; add 0.2-2 parts of binder, stir and disperse at a speed of 700-1000rpm for 15-35min; add 0.05-0.5 parts of thickener, stir and disperse at a speed of 800-1200rpm for 10-30min; add 0.0001-0.01 parts of wetting agent, stir and disperse at a speed of 700-900rpm for 25-50min; obtain a uniformly dispersed POSS-(PMMA)8 slurry, transfer the slurry to a finished product container, and keep stirring at a low speed to prevent the slurry from settling.
[0045] Step 3: Coating of modified slurry:
[0046] The modified slurry prepared in the second step is coated on the surface of the diaphragm base film by using a gravure method, a spraying method, etc., and the moisture is dried in an oven to obtain a POSS-(PMMA)8 coated diaphragm.
[0047] The present invention solves the technical problem by introducing a new type of modified material, PMMA (POSS-(PMMA)8) modified by cage-type polysilsesquioxane (POSS), as a coating material for the diaphragm. By utilizing the excellent mechanical properties and thermal stability of POSS and the good electrolyte wettability and processability of PMMA, the two are combined through the above-mentioned chemical synthesis method to obtain a diaphragm material with improved mechanical strength, thermal stability and electrolyte wettability. This modification method not only improves the comprehensive performance of the diaphragm, reduces the internal resistance of the battery cell, increases the hardness and safety performance of the battery cell, but also overcomes the problems of high cost and uncertain supply of the original PVDF coating material. By adjusting the concentration and molecular weight of POSS-(PMMA)8, the present invention further optimizes the performance of the coating diaphragm, making it more suitable for the requirements of high-performance lithium-ion batteries, showing great application potential. This method provides a cost-effective and excellent lithium-ion battery diaphragm modification technology, which helps to promote the progress and application of lithium-ion battery technology.
[0048] The technical solution of the present invention will be specifically described below in conjunction with embodiments and comparative examples.
[0049] Embodiment 1
[0050] Preparation of POSS-(PMMA)8
[0051] At room temperature, 100 parts of C7H8O, 1 part of POSS-(C3H6Cl)8, 96 parts of MMA, 2 parts of PMDETA and 1 part of CuCl were gradually added into a flask according to the molar ratio, a magnetic rotor was added, and the flask with a stopper was placed in liquid nitrogen for cooling. The air in the flask was evacuated by a vacuum pump and filled with high-purity nitrogen to remove oxygen and water vapor in the flask. The flask was thawed and then frozen again, and the process was repeated three times. The flask was stirred magnetically at 80°C, reacted for 12 hours, and the product was extracted by precipitation, filtration and drying to obtain modified POSS-(PMMA)8 powder.
[0052] Preparation of coating slurry
[0053] Add 0.6 parts of vinyl bisstearamide to 65 parts of deionized water according to the mass ratio, and stir and disperse at a speed of 800 rpm for 10 minutes; add 30 parts of POSS-(PMMA)8 powder into the container, and stir and disperse at a speed of 1000 rpm for 60 minutes; add 1.5 parts of polyvinyl alcohol, and stir and disperse at a speed of 800 rpm for 30 minutes; add 0.1 parts of carboxymethyl cellulose, and stir and disperse at a speed of 900 rpm for 25 minutes; add 0.0001 parts of sodium dodecyl sulfate, and stir and disperse at a speed of 900 rpm for 25 minutes; obtain a uniformly dispersed POSS-(PMMA)8 slurry, transfer the slurry to a finished product container, and keep stirring at a low speed to prevent the slurry from settling.
[0054] Preparation of coated diaphragms
[0055] The slurry prepared in the previous step was coated on a polyethylene diaphragm with a thickness of 12 μm by a micro-gravure method, and the coating thickness was 2 μm. The moisture was dried in an oven to obtain a POSS-(PMMA)8 coated diaphragm.
[0056] Embodiment 2
[0057] At room temperature, 100 parts of C7H8O, 3 parts of POSS-(C3H6Cl)8, 94 parts of MMA, 2 parts of PMDETA and 1 part of CuCl were gradually added into a flask according to the mass ratio, a magnetic rotor was added, and the flask with a stopper was placed in liquid nitrogen for cooling. The air in the flask was evacuated by a vacuum pump and filled with high-purity nitrogen to remove oxygen and water vapor in the flask. The flask was thawed and then frozen again, and the process was repeated three times. The flask was stirred magnetically at 80°C, reacted for 12 hours, and the product was extracted by precipitation, filtration, drying and obtaining a modified POSS-(PMMA)8 powder.
[0058] Preparation of coating slurry
[0059] Add 0.5 parts of vinyl bisstearamide to 65 parts of deionized water according to the mass ratio, and stir and disperse at a speed of 800 rpm for 10 minutes; add 30 parts of POSS-(PMMA)8 powder into the container, and stir and disperse at a speed of 1000 rpm for 60 minutes; add 1.5 parts of polyvinyl alcohol, and stir and disperse at a speed of 800 rpm for 30 minutes; add 0.15 parts of carboxymethyl cellulose, and stir and disperse at a speed of 900 rpm for 25 minutes; add 0.0001 parts of sodium dodecyl sulfate, and stir and disperse at a speed of 900 rpm for 20 minutes; obtain a uniformly dispersed POSS-(PMMA)8 slurry, transfer the slurry to a finished product container, and keep stirring at a low speed to prevent the slurry from settling.
[0060] Preparation of coated diaphragms
[0061] The slurry prepared in the previous step was coated on a polyethylene diaphragm with a thickness of 12 μm by a micro-gravure method, and the coating thickness was 2 μm. The moisture was dried in an oven to obtain a POSS-(PMMA)8 coated diaphragm.
[0062] Embodiment 3
[0063] At room temperature, 100 parts of C7H8O, 5 parts of POSS-(C3H6Cl)8, 92 parts of MMA, 2 parts of PMDETA and 1 part of CuCl were gradually added to the flask according to the mass ratio, a magnetic rotor was added, and the flask with a stopper was placed in liquid nitrogen for cooling. The air in the flask was evacuated by a vacuum pump and filled with high-purity nitrogen to remove the oxygen and water vapor in the flask. The flask was thawed and then frozen again, and the process was repeated three times. The flask was stirred magnetically at 80°C, reacted for 12 hours, and the product was extracted by precipitation, filtration and drying. The modified POSS-(PMMA)8 powder was obtained.
[0064] Preparation of coating slurry
[0065] Add 0.4 parts of vinyl bisstearamide to 65 parts of deionized water according to the mass ratio, and stir and disperse at a speed of 800 rpm for 10 minutes; add 30 parts of POSS-(PMMA)8 powder into the container, and stir and disperse at a speed of 1000 rpm for 60 minutes; add 1.5 parts of polyvinyl alcohol, and stir and disperse at a speed of 800 rpm for 30 minutes; add 0.2 parts of carboxymethyl cellulose, and stir and disperse at a speed of 900 rpm for 25 minutes; add 0.0001 parts of sodium dodecyl sulfate, and stir and disperse at a speed of 900 rpm for 20 minutes; obtain a uniformly dispersed POSS-(PMMA)8 slurry, transfer the slurry to a finished product container, and keep stirring at a low speed to prevent the slurry from settling.
[0066] Preparation of coated diaphragms
[0067] The slurry prepared in the previous step was coated on a polyethylene diaphragm with a thickness of 12 μm by a micro-gravure method, and the coating thickness was 2 μm. The moisture was dried in an oven to obtain a POSS-(PMMA)8 coated diaphragm.
[0068] Embodiment 4
[0069] At room temperature, 100 parts of C7H8O, 8 parts of POSS-(C3H6Cl)8, 89 parts of MMA, 2 parts of PMDETA and 1 part of CuCl were gradually added to the flask according to the mass ratio, a magnetic rotor was added, and the flask with a stopper was placed in liquid nitrogen for cooling. The air in the flask was evacuated by a vacuum pump and filled with high-purity nitrogen to remove oxygen and water vapor in the flask. The flask was thawed and then frozen again, and repeated three times. The flask was stirred magnetically at 80°C, reacted for 10 hours, and the product was extracted by precipitation, filtration and drying. The modified POSS-(PMMA)8 powder was obtained.
[0070] Preparation of coating slurry
[0071] Add 0.3 parts of vinyl bisstearamide to 65 parts of deionized water according to the mass ratio, and stir and disperse at a speed of 800 rpm for 10 minutes; add 30 parts of POSS-(PMMA)8 powder into the container, and stir and disperse at a speed of 1000 rpm for 60 minutes; add 1.5 parts of polyvinyl alcohol, and stir and disperse at a speed of 800 rpm for 30 minutes; add 0.3 parts of carboxymethyl cellulose, and stir and disperse at a speed of 900 rpm for 25 minutes; add 0.0001 parts of sodium dodecyl sulfate, and stir and disperse at a speed of 900 rpm for 20 minutes; obtain a uniformly dispersed POSS-(PMMA)8 slurry, transfer the slurry to a finished product container, and keep stirring at a low speed to prevent the slurry from settling.
[0072] Preparation of coated diaphragms
[0073] The slurry prepared in the previous step was coated on a polyethylene diaphragm with a thickness of 12 μm by a micro-gravure method, and the coating thickness was 2 μm. The moisture was dried in an oven to obtain a POSS-(PMMA)8 coated diaphragm.
[0074] Comparative Example
[0075] Preparation of coating slurry
[0076] Add 0.5 parts of vinyl bisstearamide to 65 parts of deionized water according to the mass ratio, and stir and disperse at a speed of 800 rpm for 10 minutes; add 30 parts of commercial PMMA powder into the container, and stir and disperse at a speed of 1000 rpm for 60 minutes; add 1.5 parts of polyvinyl alcohol, and stir and disperse at a speed of 800 rpm for 30 minutes; add 0.15 parts of carboxymethyl cellulose, and stir and disperse at a speed of 900 rpm for 25 minutes; add 0.0001 parts of sodium dodecyl sulfate, and stir and disperse at a speed of 900 rpm for 20 minutes; obtain a uniformly dispersed PMMA slurry, transfer the slurry to a finished product container, and keep stirring at a low speed to prevent the slurry from settling.
[0077] Preparation of coated diaphragms
[0078] The slurry prepared in the previous step was coated on a polyethylene diaphragm with a thickness of 12 μm by a micro-gravure method, and the coating thickness was 2 μm. The moisture was dried in an oven to obtain a POSS-(PMMA)8 coated diaphragm.
[0079] The coated diaphragms obtained in Examples 1 to 4 and the comparative examples were tested, and the specific test methods are as follows:
[0080] 1.Thickness test:
[0081] The thickness of the lithium battery separator was tested using a thickness gauge provided by Mahr according to the standard GB / T6672-2001.
[0082] 2. Surface density test:
[0083] The weighing method equipment provided by Mettler Toledo was used to measure the surface density. The surface density of the lithium battery separator was tested according to the ASTM D792-13 international standard.
[0084] 3. Air permeability test:
[0085] The test equipment used was a Gurley type air permeability tester provided by Gurley Company. The air permeability of the lithium battery separator prepared in the example was tested according to the ASTM D7264-16 international standard, specifically by clamping the sample between two annular clamps, applying differential pressure and quantitatively analyzing the air flow to determine the air permeability of the sample.
[0086] 4.120℃*1h thermal shrinkage test method:
[0087] The membrane sample was cut into a size of 10 cm × 10 cm, and the surface of the sample was ensured to be flat.
[0088] The sample was placed in a TYL-6C series digital heat shrink instrument manufactured by Weihai Tianyuan Precision Machinery Co., Ltd., the temperature was set to 120°C, and the constant temperature mode was selected to keep the sample stable at 120°C.
[0089] Under constant temperature conditions, record the initial dimensions (length, width).
[0090] The sample was heated at 120 °C for 1 h to allow it to reach thermal shrinkage equilibrium.
[0091] After the heat shrinkage was completed, the dimensions (length, width) of the sample were measured again.
[0092] Calculate the MD heat shrinkage and TD heat shrinkage (MD is the longitudinal direction, i.e. the continuous film-making direction of the diaphragm when stretched, and TD is the transverse direction, i.e. the direction perpendicular to MD):
[0093] MD heat shrinkage rate = [(initial length - length after heat shrinkage) / initial length] × 100%
[0094] TD heat shrinkage rate = [(initial width - width after heat shrinkage) / initial width] × 100%
[0095] 5.Tensile strength and elongation at break test:
[0096] The tensile strength and TD and MD elongation at break of the diaphragm were tested using an AGS-X electronic universal testing machine produced by SHIMADZU according to the provisions of GB / T1040.3-2006 standard.
[0097] 6. Puncture strength
[0098] The diaphragm was tested using the AGS-X electronic universal tester produced by SHIMADZU. The sample was clamped on the instrument and a needle with a spherical end and a diameter of 1.0 mm was used to apply force at a speed of 2.0 mm / s until the diaphragm was punctured. The maximum force value reached during puncture was recorded as the puncture strength.
[0099] The experimental results are shown in the following table:
[0100]
[0101] As can be seen from the above table, compared with the coated diaphragm made of common PMMA microparticles that are not modified, the mechanical property of the coated diaphragm obtained by utilizing modified PMMA in the embodiment is better, and POSS can better realize the transmission and release of stress and heat energy as hard segment, so tensile strength and thermal shrinkage performance are significantly improved. Simultaneously due to the increase of the overall size of the molecular chain and the addition of hard segment, the dimensional stability of PMMA is increased, and it is not easy to block the diaphragm aperture, so that air permeability is better. Contrast four embodiments, the diaphragm performance obtained by embodiment three is better than embodiment one, two and four, and it can be seen that the addition amount of initiator POSS-(C3H6Cl)8 is not the more the better, and the initiator accounts for too much and can cause the prepared POSS-(PMMA)8 performance degradation thereby causing the reduction of coated diaphragm performance.
[0102] In summary, the modified PMMA particles and their coated diaphragms prepared by the present invention have better mechanical properties and thermal stability than traditional PMMA coated diaphragms. At the same time, the increase in the overall size of the molecular chain and the addition of hard segments make it less likely to block the pore size of the diaphragm, thereby improving its air permeability. In theory, it can reduce its internal resistance and has great application potential.
[0103] The above embodiments are only used to illustrate the technical solution of the present application and are not intended to limit it. Although the present application has been described in detail with reference to the preferred embodiments, a person skilled in the art should understand that the technical solution of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present application.
Claims
1. A method for modifying a lithium battery separator, characterized in that: The modification method comprises the following steps: With anisole as solvent, octachloropropylsilsesquioxane as initiator, methyl methacrylate as monomer, cuprous chloride as catalyst, and pentamethyldiethylenetriamine as ligand, polymethacrylic acid-cage polysilsesquioxane powder POSS-(PMMA)8 is synthesized by atom transfer radical polymerization, specifically, by weight: 100 parts of anisole, 1-8 parts of octachloropropylsilsesquioxane, 1-3 parts of pentamethyldiethylenetriamine, 0.5-2 parts of cuprous chloride, and 89-96 parts of methyl methacrylate MMA are gradually added into a flask, and then the flask with a bottle stopper is placed in liquid nitrogen, the air in the flask is evacuated by a vacuum pump, and high-purity nitrogen is filled into the flask to remove oxygen and water vapor in the flask, and the flask is thawed and then frozen for three times, and the reaction is carried out at 80° C. for 6-12 hours, and the product is extracted by precipitation and filtration to obtain polymethacrylic acid-cage polysilsesquioxane powder POSS-(PMMA)8; The synthesized polymethacrylic acid-cage polysilsesquioxane powder is prepared into a modified slurry containing polymethacrylic acid-cage polysilsesquioxane, and the preparation of the modified slurry includes: adding deionized water, dispersant, polymethacrylic acid-cage polysilsesquioxane powder, binder, thickener and wetting agent according to mass ratio, and mixing and stirring; by mass parts: the addition amount of the deionized water is 30-90 parts, the addition amount of the dispersant is 0.3-1 parts, the addition amount of the polymethacrylic acid-cage polysilsesquioxane powder is 10-40 parts, the addition amount of the binder is 0.2-2 parts, the addition amount of the thickener is 0.05-0.5 parts, and the addition amount of the wetting agent is 0.0001-0.01 parts; The modified slurry is coated on the surface of the diaphragm base film and dried to obtain a polymethacrylate-cage-type polysilsesquioxane coated diaphragm. The modified slurry is coated on the surface of the diaphragm base film by a gravure method or a spray method, and the water is dried in an oven to obtain a polymethacrylate-cage-type polysilsesquioxane coated diaphragm.
2. The modification method according to claim 1, characterized in that: Add 0.3-1 part of dispersant to 30-90 parts of deionized water by mass ratio and stir and disperse at 800-1200 rpm for 5-20 minutes; Add 10-40 parts of polymethacrylic acid-cage polysilsesquioxane powder, and stir and disperse at 800-1500 rpm for 40-80 minutes; Add 0.2-2 parts of binder, stir and disperse at 700-1000 rpm for 15-35 minutes; Add 0.05-0.5 parts of thickener, and stir and disperse at 800-1200 rpm for 10-30 minutes; Add 0.0001-0.01 parts of wetting agent and stir and disperse at 700-900 rpm for 25-50 minutes; A modified slurry containing polymethacrylic acid-cage polysilsesquioxane is obtained.
3. The modification method according to claim 2, characterized in that: The method also includes transferring the obtained modified slurry into a finished product container and maintaining low-speed stirring to prevent the slurry from settling.
4. The modification method according to claim 1, characterized in that: In the preparation process of the polymethacrylate-cage polysilsesquioxane powder, the molecular weight of the obtained polymethacrylate-cage polysilsesquioxane is adjusted by adjusting the ratio of octachloropropyl silsesquioxane to methyl methacrylate.
5. A lithium ion battery separator, characterized in that: The invention is prepared by the modification method according to any one of claims 1 to 4, comprising a polymethacrylic acid-cage polysilsesquioxane coating and a diaphragm base film layer, wherein the polymethacrylic acid-cage polysilsesquioxane coating is formed by coating a modified slurry containing polymethacrylic acid-cage polysilsesquioxane on the surface of the diaphragm base film.
6. A lithium ion battery separator according to claim 5, characterized in that: The diaphragm base film is selected from one of polyethylene, polypropylene or a multi-layer composite diaphragm.
Citation Information
Patent Citations
Star silsesquioxane-grafted acrylic ester-sulfonated styrene segmented copolymer and preparation method thereof
CN103172805A
Gel electrolyte with high thermal and mechanical property of nanocomposite POSS-polyacrylate coated and modified polyolefin separator and preparation method of gel electrolyte
CN107221625A